Leading and managing people in education - Bush, Tony 1943-; Middlewood, David (Los Angeles SAGE, 2013)
This book deals with the essential task of leading and managing staff in educational organizations.
Includes bibliographical references and indexes.
Keywords: Educational leadership; School personnel management; School management and organization